Memória e atividade elétrica neuronal do hipocampo após ressecção na epilepsia do lobo temporal - Azambuja, Luciana Schermann (2011)
Aim: To investigate the correlation between neuronal electrical activity (viability) in human hippocampal slices in vitro and post-operative memory performance of patients submitted to epilepsy surgery due to temporal mesial sclerosis.Methods: The sample comprised 64 patients with temporal lobe epilepsy refractory to drug treatment submitted to selective amygdalohippocampectomy. We compared patients who had hippocampal slices generating electrical activity (viable) with those whose results did not show electrophysiological findings in vitro (non-viable). Memory performance was assessed through the Wechsler Memory Scale Revised (WMS-R). The variables investigated were immediate verbal memory, delayed verbal memory, immediate visual memory and delayed visual memory in the pre- and post-operative periods.Results: There was a statistically significant improvement in the group with hippocampal slices without electrical activity (non-viable), mainly as regards delayed verbal memory (p=0.012). In immediate and delayed visual memory there was an important improvement as well in the non-viable group, yet statistically insignificant. In the viable group only delayed verbal memory was enhanced, with a slight positive effect after withdrawal of the hippocampus. The most important difference between the groups was found in right hemisphere resections, where the results were not significant for delayed verbal memory in the viable group and there was a significant improvement of this variable in the non-viable group. In left hemisphere resections there was improved performance of delayed verbal memory in both groups.Conclusion: The non-viable group correlated better with post-operative memory performance, i.e. patients where hippocampal slices without electrical activity were resected had good memory outcomes after surgery.